Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Turnover Intention pada bagian Produksi Tripacific Electrindo - Fauzia, Maharrani Syifa; Seleman Hardi Yahawi (Journal of Management and Bussines (JOMB), 2025)
This study aims to determine the effect of workload and work environment on turnover intention in the production department of PT. Tripacific Electrindo. This research uses a quantitative method. The sample consists of 76 respondents, selected using random sampling technique and calculated using Slovin's formula. Data collection was done by distributing questionnaires to employees of PT. Tripacific Electrindo. Data analysis was performed using SPSS version 27. The results of this study show that workload has a positive and significant effect on turnover intention, with a t-value of 22.186 > t-table value of 1.993 and a significant value of 0.001 < 0.05. The work environment has a negative and significant effect on turnover intention, with a t-value of -1.343 < 1.993 and a significant value of 0.183 > 0.05. Simultaneously, workload and work environment have a positive and significant effect on turnover intention, as shown by an F-value of 254.683 > F-table value of 3.12. The coefficient of determination test shows a value of 87.5%, meaning that the contribution of the effect of workload and work environment on turnover intention is 87.5%, while 12.5% is influenced by other variables outside of the variables studied in this research.   Keywords: Workload, Work Environment, Turnover Intention